2006
DOI: 10.1007/s00330-005-0055-7
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body MRI in the detection of bone marrow infiltration in patients with plasma cell neoplasms in comparison to the radiological skeletal survey

Abstract: To compare the diagnostic value of whole-body MRI versus radiological skeletal survey (RSS) in staging patients with plasma cell neoplasms (PCN) and to evaluate the possible therapeutic impact of the replacement of RSS by whole-body MRI. Fifty-four patients with PCN [multiple myeloma (MM), n=47; monoclonal gammopathy of unknown significance (MGUS), n=7] were studied by whole-body MRI and RSS in a monocenter prospective analysis from August 2002 to May 2004. The MRIs were performed using a rolling table platfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(36 citation statements)
references
References 31 publications
0
36
0
Order By: Relevance
“…For example, the introduction of a rolling-table platform with integrated surface coils has eliminated previously time-consuming changes in position of both patient and coils, and sequences such as breath-hold gradient echo and whole-body turbo STIR have substantially shortened scan time-in some cases to a total scan time of less than 15 min-while also providing good spatial resolution [56][57][58]. Given its high sensitivity in the detection of Fig.…”
Section: Complementary Mr Techniques Under Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the introduction of a rolling-table platform with integrated surface coils has eliminated previously time-consuming changes in position of both patient and coils, and sequences such as breath-hold gradient echo and whole-body turbo STIR have substantially shortened scan time-in some cases to a total scan time of less than 15 min-while also providing good spatial resolution [56][57][58]. Given its high sensitivity in the detection of Fig.…”
Section: Complementary Mr Techniques Under Developmentmentioning
confidence: 99%
“…The amount of residual viable tumor cannot be assessed by visual inspection of the MR image or gross specimen. Histopathologic analysis using the Huvos method determined that 40% of the remaining lesion was necrotic, indicating a poor (grade I) chemotherapeutic response marrow lesions and excellent soft tissue contrast, WBMRI is under investigation as a screening and staging modality in oncology patients [56][57][58][59][60][61]. For example, WBMRI appears to be both more sensitive and specific than radiographic skeletal survey in assessing the extent of multiple myeloma, which is critical in determining the appropriate therapy [58,59].…”
Section: Complementary Mr Techniques Under Developmentmentioning
confidence: 99%
“…7 Although PR has been an integral part of imaging for the last 25 years, osteolytic lesions can only be detected on plain films if more than 50% of bone loss is evident. 8 For this reason, CT is most often recommended because it is more sensitive to depict destruction of mineralized bone and imminent osseous instability, especially in the vertebral column. However, myeloma infiltrates inside cancellous bone are difficult to detect as long as stimulation of osteoclast activity has not yet taken place to a major extent and the bone trabeculae are still preserved.…”
mentioning
confidence: 99%
“…8,[12][13][14] MRI has a sensitivity of 68%, a specificity of 83%, a positive predictive value of 88% and is superior to PET-CT. 15 Furthermore, the development of fast sequences allows MRI to be performed as a whole-body protocol (wb-MRI), replacing the use of spinal MRI alone. 16 Focal lesions and diffuse tumor cell infiltration detected by wb-MRI have been demonstrated to be of prognostic significance for predicting progression free and overall survival in monoclonal plasma cell diseases.…”
mentioning
confidence: 99%
“…51 When whole-body examination was performed, including the appendicular skeleton, MRI had a higher detection rate than WBXR. 57 A comparison of axial MRI versus whole body MRI revealed that~1 0% of patients had lesions exclusively outside of the axial skeleton. 58 A systematic review of imaging techniques in the diagnosis of myeloma bone disease compared MRI with WBXR and/or CT.…”
Section: Imagingmentioning
confidence: 99%